Odpowiedzi

2010-04-14T18:10:15+02:00
X- 1a
y- 1b

x+y=67
60%x + 75%y = 45

x+y=67
0,6x + 0,75y = 45

x=67-y
0,6 * ( 67 -y ) + 0,75y = 45

x=67-y
40,2 - 0,6 y + 0,75 y = 45

x=67-y
0,15y = 4,8 / :0,15

x=67-y
y=32

x=67-y
y=32

x=35
y=32
2010-04-14T18:13:58+02:00
Ia- x
Ib- y
x+y= 67
60%x+75%y= 45
x+y= 67
0.6x +0.75y = 45

x= 67- y
0.6×( 67 - y) + 0.75 y = 45

x= 67-y
40,2 - 0.6y +0.75y = 45
40,2 +0,15y = 45/ 40,2
0,15y= 4,8/÷ 0,15
y= 32 uczniowie kl B

x= 67- 32
x= 35 uczniowie kl A

35+32=67
0,6× 35 = 0,75×32= 21+24=45